1992
DOI: 10.1017/s0021859600071513
|View full text |Cite
|
Sign up to set email alerts
|

Varietal differences in the chemical composition and in vitro digestibility of rice straw

Abstract: SummaryFour varieties of rice straw, MRl, MR71, MR84 and MR27, were separated into the following botanical fractions; inflorescence, stem, leaf blade and leaf sheath. The relative proportion of each fraction in whole straw was estimated and analysed for its chemical composition and in vitro digestibility (IVD). The composition and IVD of whole straw was then calculated. Cluster analysis showed that MRl was distinct from the other varieties. This could be attributed to a high proportion of stem (32·3%), high IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…The morphological composition of the present six varieties was similar to the varieties reported by Vadiveloo (1992) but varied from the varieties reported by Vadiveloo (1995) being higher in leaf content. The absolute values for constant a and constant b for untreated straw (Tables 3 and 4) were lower than similar values obtained by the nylon bag or gas production techniques (Walli et al, 1988;Nakashima and 0rskov, 1990;Shen et al, 1998b) probably because cellulase dry matter degradation only mimics part of the complex process taking place in the rumen (Lopez et al, 1998).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The morphological composition of the present six varieties was similar to the varieties reported by Vadiveloo (1992) but varied from the varieties reported by Vadiveloo (1995) being higher in leaf content. The absolute values for constant a and constant b for untreated straw (Tables 3 and 4) were lower than similar values obtained by the nylon bag or gas production techniques (Walli et al, 1988;Nakashima and 0rskov, 1990;Shen et al, 1998b) probably because cellulase dry matter degradation only mimics part of the complex process taking place in the rumen (Lopez et al, 1998).…”
Section: Discussionsupporting
confidence: 79%
“…Studies on the nutritive value of Malaysian rice straw varieties have employed cellulase to estimate end-point digestion (Vadiveloo, 1992(Vadiveloo, , 1995. As the degradation characteristics of Malaysian rice straw varieties have not been documented, the present study was initiated.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the improvement of IVDMD and IVOMD depends on the forage chemical characteristics and the supplement used, corroborating with Morgavi et al (2000), who stated that more detailed knowledge of the interaction between the supplement with the forage, the host, and the rumen microorganisms is necessary for the correct application of this technology. Previous research had also identified variation in rice straw digestibility (Vadiveloo, 1992;Vadiveloo, 1995) and improvement of forage in vitro digestibility with the use of mineral and protein-energy supplement (Barbosa et al, 2007) and exogenous fibrolytic enzyme (Beauchemin et al, 2003;Bassiouni et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Varietal differences in IVDMD of rice straw have been reported from many countries and have been first summarized by Doyle et al [91]. Vadiveloo [177] observed later a whole plant IVDMD ranging from 23.6 to 36.9 in rice straws, when the IVDMD of stems ranged from 27.6 to 43.3%. Agbagla-Dohnani et al [4] observed an in sacco degradability of organic matter in straws of 15 rice varieties ranging from 23.6 to 35.6%.…”
Section: Genetic Variation In Cell Wall Digestibility Estimated From mentioning
confidence: 96%